2011
DOI: 10.1037/a0024630
|View full text |Cite
|
Sign up to set email alerts
|

Faculty women of color: The critical nexus of race and gender.

Abstract: This article examines the experiences of faculty women of color at predominately White public research extensive universities. In the wake of legal challenges to affirmative action, such as Gratz and Grutter, and the proliferation of antiaffirmative action state “Civil Rights Initiatives,” these issues become critically important. This study's central questions were, “What are the lived experiences of faculty women of color in predominately White institutions? ” and “What are the implications of legal challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
138
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(141 citation statements)
references
References 38 publications
2
138
0
1
Order By: Relevance
“…This is because the experiences and advancement of faculty members vary significantly not only based on their sex but also depending on their ethnicity (Johnson-Bailey and Cervero 2008;Turner et al 2011). A limitation of this study is that the depart ments' website data used to collect information about faculty members covered a restricted range of content.…”
Section: Discussion a N D C O N C L U S Io N Smentioning
confidence: 99%
“…This is because the experiences and advancement of faculty members vary significantly not only based on their sex but also depending on their ethnicity (Johnson-Bailey and Cervero 2008;Turner et al 2011). A limitation of this study is that the depart ments' website data used to collect information about faculty members covered a restricted range of content.…”
Section: Discussion a N D C O N C L U S Io N Smentioning
confidence: 99%
“…A Latina chemical engineer noted that "students tend to basically just have a certain level of respect for a male faculty from day one that they don't necessarily have for a female faculty, or for me at least . " Prior studies have made similar observations (Turner, Gonzáles, & Wong, 2011;Stanley, 2006 (citing studies)) .…”
Section: Students' Negative Competence Assumptionsmentioning
confidence: 65%
“…Academic literature on women academic administrators revealed that the priority of family obligations act as the strongest challenge to women academicians who want to move in administrative positions (Luke, 2000;Oplatka, 2006;Eagly & Carli, 2007;Madsen, 2008;Neale & Ozkanli, 2010;Turner, 2011Turner, , 2012Eagly, 2012;Peterson, 2014;Afiouni, 2014;Evetts, 2014). The finding of this study is in agreement with previously mentioned literature which believes women, mostly because of traditional gender role expectations, more than men are expected to tolerate home responsibilities such as care of children, husband, aged parent and the obligatory house work, even if they are managers in their career.…”
Section: Findings and Discussionmentioning
confidence: 99%